Hierarchically-Designed 3D Flower-Like Composite Nanostructures as an Ultrastable, Reproducible, and Sensitive SERS Substrate - Yueksel, Sezin; Ziegler, Mario; Goerke, Sebastian; Huebner, Uwe; Weber, Karina; Schaaf, Peter; Meyer, Hans-Georg; Cialla-May, Dana; Popp, Juergen (ACS Applied Materials and Interfaces, 2017)
Surface-enhanced Raman spectroscopy (SERS) is an attractive tool in the analytical sciences due to its high specificity and sensitivity. Because SERS-active substrates are only available as two-dimensional arrays, the fabrication of three-dimensional (3D) nanostructures allows for an increased number of hot spots in the focus volume, thus further amplifying the SERS signal. Although a great number of fabrication strategies for powerful SERS substrates exist, the generation of 3D nanostructures with high complexity and periodicity is still challenging. For this purpose, we report an easy fabrication technique for 3D nanostructures following a bottom-up preparation protocol. Enzymatically generated silver nanoparticles (EGNPs) are prepared, and the growth of hierarchically-designed 3D flower-like silica-silver composite nanostructures is induced by applying plasma-enhanced atomic layer deposition (PE-ALD) on the EGNPs. The morphology of these nanocomposites can be varied by changes in the PE-ALD cycle number, and a flower height of up to 10 μm is found. Moreover, the metallized (e.g., silver or gold) 3D nanostructures resulting from 135 PE-ALD cycles of silica creation provide highly reproducible SERS signals across the hydrophobic surface. Within this contribution, the morphological studies, optical properties, as well as the SERS response of these metallized silica-silver composite nanostructures applying vitamin B2 as a model analyte are introduced.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 3D flower-like silica-silver nanostructures; hybrid materials; PE-ALD; riboflavin (vitamin B2); SERS substrates; SERS templates